Analisis Tantangan Konsumen Mendapatkan Pengembalian Dana Terhadap Barang Tidak Sesuai di Platform Toko Online - Syammulya, Bagas Wisnu; Ramadhan, Aditya Rizky (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Many facets of society have altered as a result of information and communication technology advancements, including how consumers purchase online. However, issues like non-conformity of goods, which lead to a rise in refund claims, are frequently brought on by the indirect character of transactions. This study makes use of qualitative approaches, literature reviews, and empirical procedures. The findings indicate that while UUPK provides a suitable legal framework concerning rights and obligations in online transactions, other challenges remain to be addressed before UUPK can be implemented. To guarantee the best possible consumer protection, business actors, consumers, and effective legislation must work together.